The Potential of Photodynamic Therapy Using Solid Lipid Nanoparticles with Aluminum Phthalocyanine Chloride as a Nanocarrier for Modulating Immunogenic Cell Death in Murine Melanoma In Vitro - Marina M. Simões; Karen L. R. Paiva; Isadora Florêncio de Souza; Victor Carlos Mello; Ingrid Gracielle Martins da Silva; Paulo Eduardo Narcizo Souza; Luis Alexandre Muehlmann; Sônia Nair Báo (MDPI AG, 2024)
Photodynamic therapy (PDT) uses a photosensitizer to generate reactive oxygen species (ROS) that kill target cells. In cancer treatments, PDT can potentially induce immunogenic cell death (ICD), which is characterized by a well-controlled exposure of damage-associated molecular patterns (DAMPs) that activate dendritic cells (DCs) and consequently modulate the immune response in the tumor microenvironment. However, PDT still has limitations, such as the activity of photosensitizers in aqueous media and poor bioavailability. Therefore, a new photosensitizer system, SLN-AlPc, has been developed to improve the therapeutic efficacy of PDT. In vitro experiments showed that the light-excited nanocarrier increased ROS production in murine melanoma B16-F10 cells and modulated the profile of DCs. PDT induced cell death accompanied by the exposure of DAMPs and the formation of autophagosomes. In addition, the DCs exposed to PDT-treated B16-F10 cells exhibited morphological changes, increased expression of MHCII, CD86, CD80, and production of IL-12 and IFN-γ, suggesting immune activation towards an antitumor profile. These results indicate that the SLNs-AlPc protocol has the potential to improve PDT efficacy by inducing ICD and activating DCs.